Low body mass index is associated with diminished plasma cytokines and chemokines in both active and latent tuberculosis - Kumar, Nathella Pavan; Nancy, Arul P.; Moideen, Kadar; Menon, Pradeep A.; Banurekha, Vaithilingam V.; Nair, Dina; Nott, Sujatha; Babu, Subash (Frontiers in Nutrition, 2023)
Introduction Low body mass index (BMI) is a major risk factor for tuberculosis (PTB). Low BMI can impair the immune system and thus might affect TB incidence. Methods We examined the plasma levels of Type 1, Type 17, pro-inflammatory, Type 2 and regulatory cytokines and CC and CXC chemokines in PTB and latent TB (LTB) individuals with low BMI (LBMI) or normal BMI (NBMI). Results Our data show that PTB is associated with significantly lower levels of IFNγ, TNFα, IL-2, IL-17A, IL-6, IL-12, IL-4 and IL-5 cytokines but significantly higher levels of IL-10, TGFβ and GM-CSF in LBMI compared to NBMI. Similarly, PTB is also associated with significantly lower levels of CCL2, CCL3, CCL11, CXCL1, CXCL9 and CXCL10 chemokines in LBMI compared to NBMI. Our data reveals that LTB is associated with significantly lower levels of IFNγ, TNFα, IL-2, IL1β, IL-12, IL-13 cytokines but significantly higher levels of IL-10, TGFβ, IL-4 and IL-22 in LBMI compared to NBMI. Similarly, LTB is also associated with significantly lower levels of CCL2, CXCL1, CXCL9 and CXCL10 and significantly higher levels of CCL1, CCL3, and CCL4 in LBMI compared to NBMI. Conclusion Thus, LBMI has a major impact on the cytokine and chemokine milieu of both PTB and LTB and might predispose to the increased risk of tuberculosis by this immunomodulatory effect.